(untitled) (AmS-Skrifter, 2026)
In this article, the Mero-Jewel project (BRAIN-be 2.0) presents its first production-focused research results regarding iron-cased cloisonné brooches from the Merovingian cemetery of Harmignies. The aim is to elucidate technical aspects of production to possible differentiate artisanal tendencies or shared knowledge, which would help identify the network of production and exchange in which these objects circulated. To this effect, the composition of these brooches is discussed, and key observations are made regarding techniques, material composition and decoration. While specific workshops remain undefined, the article discusses future avenues of research while considering the large amount of data retrieved from this relatively small, yet representative sample.